Supplementary private health insurance in selected countries : lessons for EU governments? - Sebastian Gechert (Center for Economic Studies and ifo Institute (CESifo), 2009)
A famous idea to maintain affordable health expenditures is to cut back statutory health insurance (SHI) to a basic insurance and to introduce supplementary private health insurance (PHI), permitted to cover the remaining benefits and to apply managed care mechanisms. The measure is supposed to lower public health expenditures and to enhance cost efficiency and quality of service. To test these reasonings, the paper draws empirical evidence from the health systems of Australia, Canada and Switzerland. PHI fails to meet the claims in these countries, since it performs worse than SHI concerning cost development and cannot be expected to improve quality. Cream skimming and adverse selection arise instead. Therefore, regulations and incentives are necessary, but they might counteract the aim of lowering public health expenditures.
Keywords: H51; G22; I11; I18; L10; 330; private health insurance; supplementary; country survey; Private Krankenversicherung; Gesetzliche Krankenversicherung; Adverse Selection; Gesundheitskosten; Australien; Kanada; Schweiz